2004
DOI: 10.1039/b409526j
|View full text |Cite
|
Sign up to set email alerts
|

Calix[4]arene methylenebisphosphonic acids as calf intestine alkaline phosphatase inhibitors

Abstract: Calix[4]arenes bearing one or two methylenebisphosphonic acid fragments were prepared via addition of diethylphosphite to the parent calix[4]arene aldehydes. The resulting compounds displayed stronger inhibition of calf intestine alkaline phosphatase than simple methylenebisphosphonic or 4-hydroxyphenyl methylenebisphosphonic acids. The action of these phosphorylated calix[4]arenes is concordant with partial mixed-type inhibition. The inhibition constants Ki and Ki' for the calix[4]arene bis(methylenebisphosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 22 publications
1
49
0
2
Order By: Relevance
“…88 In order to study phosphorylation which occurs in biochemical processes, the phosphatase inhibitory properties of compounds 28 and 29 have been investigated. 89 In these experiments it was found that the introduction of methylenebisphosphonic acid 28 onto calix [4]arene 30 to form compounds such as 33 and 34, results in the efficient inhibition of alkaline phosphatase whereas this inhibition of 28 itself is only very low. For these phosphatase inhibitory studies, calixarenes 33 and 34 containing one and two units of 28, respectively, were synthesized via the reactions of calixarene aldehydes 31 and 32.…”
Section: Methodsmentioning
confidence: 99%
“…88 In order to study phosphorylation which occurs in biochemical processes, the phosphatase inhibitory properties of compounds 28 and 29 have been investigated. 89 In these experiments it was found that the introduction of methylenebisphosphonic acid 28 onto calix [4]arene 30 to form compounds such as 33 and 34, results in the efficient inhibition of alkaline phosphatase whereas this inhibition of 28 itself is only very low. For these phosphatase inhibitory studies, calixarenes 33 and 34 containing one and two units of 28, respectively, were synthesized via the reactions of calixarene aldehydes 31 and 32.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have identified PTPs as targets for new bioactive phosphonate compounds [27,28]. It has been shown also that preorganizing phosphonic or methylenebisphosphonic acids into calix [4]arene derivatives provides a promising approach to design effective inhibitors of alkaline phosphatase [29][30][31], Yersinia protein tyrosine phosphatase [32], and PTP1B [33].…”
Section: калікс[4]арен α-гідроксифосфонові кислоти як потенційні інгіmentioning
confidence: 99%
“…[88][89][90][91] Thus, condensation of aldehydes with diethyl phosphonate, followed by sulfonylation of the α-OH with methanesulfonyl chloride and subsequent substitution by another molecule of diethyl phosphonate provides the corresponding bisphosphonates 112 (Scheme 41) in a one-pot procedure. 89 In another report, addition of tetraethyl methylene-bis-phosphonate 15b to 3-tert-butyl-4-hydroxy-1-naphthaldehyde 113a afforded 2-[3-tert-butyl-4-hydroxynaphthyl]ethenylidene-1,1-bisphosphonate, 114a. 90 In similar instance, 3-methoxy-4-hydroxy-1-naphthaldehyde 113b gave the corresponding bisphosphonate 114b (Scheme 42).…”
Section: Scheme 39mentioning
confidence: 99%